2021
DOI: 10.1155/2021/6655685
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Insulin Sensitivity Defects Induced Embryo Implantation Loss Associated with Mitochondrial Dysfunction‐Triggered Oxidative Stress

Abstract: Scope. Implantation loss is a considerable cause of early pregnancy loss in humans and mammalian animals. It is not addressed how proliferative uterine defects implicate in implantation loss. Methods and Results. Herein, a comprehensive proteomic analysis was conducted on proliferative endometria from sows with low and normal reproductive performance (LRP and NRP, respectively). Enrichment analysis of differentially expressed proteins revealed alterations in endometrial remodeling, substance metabolism (mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 60 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…The results showed the decidualization process, under which embryonic stem cells differentiate into other cell types to facilitate embryo implantation and placenta development, was halted when fatty acid beta‐oxidation was inhibited. Embryo implantation was compromised in vitro by oxidative stress caused by mitochondrial dysfunction (Chen et al, 2021). Choline deficiency alters the membrane potential of mitochondria and lowers complex I activity, which results in subsequent oxidative stress (Corbin & Zeisel, 2012; Hensley et al, 2000; Pacelli et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed the decidualization process, under which embryonic stem cells differentiate into other cell types to facilitate embryo implantation and placenta development, was halted when fatty acid beta‐oxidation was inhibited. Embryo implantation was compromised in vitro by oxidative stress caused by mitochondrial dysfunction (Chen et al, 2021). Choline deficiency alters the membrane potential of mitochondria and lowers complex I activity, which results in subsequent oxidative stress (Corbin & Zeisel, 2012; Hensley et al, 2000; Pacelli et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Despite numerous reports on the potential contribution of insulin as a metabolic stressor in obesity, the mechanism by which uterine receptivity may be compromised is still unknown. Existing literature studying this phenomenon and underlying mechanisms utilised hyperinsulinaemic animal models ( Li et al 2017 , Chen et al 2021 ), which may not accurately reflect the inner workings of human endometrium. Our findings aimed to provide insight into this gap in knowledge by using a microfluidics approach.…”
Section: Discussionmentioning
confidence: 99%
“…insulin-signalling pathway and lipid metabolism) associated with uterine dysfunction. Chen et al subsequently used insulin-resistant animal models driven by a high-fat diet and Ishikawa cells (human endometrial adenocarcinoma cells) to create in vitro implantation models and reported that insulin resistance reduces receptivity through mitochondrial dysfunction and consequent oxidative stress ( Chen et al 2021 ). Additionally, the use of a microfluidics endometrium-on-a-chip model in bovine demonstrated cellular transcriptional and secretome differences if the endometrium following exposure to physiological extremes of metabolic factors glucose and insulin in microfluidics ( De Bem et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mice on a high-fat diet (HFD) that developed insulin resistance showed that this condition impairs uterine receptivity [49]. There is a notable decrease in the mRNA levels of Lif, Msx1, and Cldn4, suggesting compromised endometrial receptivity.…”
Section: Insulin Resistance Impairs Endometrial Receptivity In Pcosmentioning
confidence: 99%
“…There is a notable decrease in the mRNA levels of Lif, Msx1, and Cldn4, suggesting compromised endometrial receptivity. Mitochondrial dysfunction and endoplasmic reticulum stress are features of peripheral insulin resistance [49]. Mitochondria play a key role in energy production, and mitochondrial dysfunction at the cellular level can affect systemic metabolic balance.…”
Section: Insulin Resistance Impairs Endometrial Receptivity In Pcosmentioning
confidence: 99%